A Short Review on the Dynamic Characteristics of Geogrid-Reinforced Soil Retaining Walls under Cyclic Loading - Min Geng (Advances in Materials Science and Engineering)
The internal force and the form of reinforced soil wall used in high-speed railway change due to the static loads of self-gravity and rail system and dynamic load of train travelling. As a kind of flexible retaining structure, the study of the dynamic characteristics of reinforced retaining walls is of great significance for its engineering application and structural analysis. In this article, recent advances in using various research methods on the dynamic characteristics of reinforced retaining walls are reviewed. Through a series of experimental studies and numerical analysis, the research progress of dynamic characteristics of reinforced retaining walls is summarized. The advantages, disadvantages, and application of various test methods are analyzed. Finally, laboratory model tests are expounded based on previous research achievements, and prospects are proposed on the development of dynamic characteristics of reinforced retaining walls.